Effects of curing angle on laminated unsaturated polyster epoxy composites structures - Tan, Teng Teng (2015)
Small and Medium Industries or Enterprises (SMI/E) in Malaysia that involved in composite industry faced a lot of challenges, ranging from raw materials, processes and product itself. The high production cost was due to the confined production floor as a result of horizontal curing plane for long hours. A solution was proposed by investigating the different curing angles (0˚, 10˚, 20˚, 30˚, 40˚, 50˚, 60˚, 70˚, 80˚ and 90˚) to find out the best curing angle via hand lay-up assisted by vacuum bagging technique at room temperature thus is able to fabricate the composite parts with similar or improved properties besides saving space. A series of four-ply laminated glass fiber composite structures were impregnated with unsaturated polyester and epoxy separately then set to cure at different curing direction. The composite structures were tested with density, tensile, flexural and hardness tests to determine the mechanical performance, and also the SEM images were examined and analysed on fracture samples. Across the samples at different curing angles from curing angles of 0˚ to 90˚, the peak performance found out to be frequently at 40˚. However, the vertically cured 90˚ composite structure found out to have improved mechanical properties (1.089 % to 4.280 %) when benchmarked with horizontal curing plane at 0˚. Curing at a tilting angle is possible to carry out. Therefore, the vertical curing of composite parts can be recommended to SMI/E in view of its improved performance and optimum space management solution.